Health benefit of olive from Islamic and Science perspective : An interrelation by the principle of maslahah - Salman, Amiruddin; Sumayyah, Abdul Aziz (2017)
Recently, olive products especially its oil was proven to have a lot of health benefit to human in term of preventive and therapeutic measures.The quality of its fruit and the content of bioactive ingredient within the olive product determine it’s efficacy to modulate certain disease. Islam as a comprehensive religion have been focusing on the health issues by implementing a good eating habits and highlighting on certain food that have a health benefit such as olive, fig, grape, dates and many more. Islamic scholars such a Ibnu Qayyim and Ibnu Sina also discussing the statements of Al-Quran and Hadith pertaining to this natural food in their books which turn out to be in the same line with current scientific evidence and the principle of Islam to gain benefit and to avoid harm (jalb al-masalih wa dar’ul almafasid) in human life. In this study, we review several papers and reports regarding various type of olive oil in the market in order to highlight about different qualities that present within different type of olive oil that can hinder the consumer from obtaining an optimum health benefits.